2019
DOI: 10.1049/iet-map.2018.5747
|View full text |Cite
|
Sign up to set email alerts
|

Isolation enhancement of densely packed array antennas with periodic MTM-photonic bandgap for SAR and MIMO systems

Abstract: A metamaterial photonic bandgap (MTM-PBG) periodic structure is used as a decoupling frame to improve the isolation between transmit-receive (T/R) sections of densely packed array antenna in synthetic aperture radar (SAR) and multiple-input multiple-output (MIMO) systems. With this technique the MTM-PBG structure is shown to effectively suppress surface wave propagations between the T/R array antennas by an average of 12 dB. MTM-PBG layer comprises a periodic arrangement of dielectric circles etched in the cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 1 publication
0
42
0
Order By: Relevance
“…In [134] an MTM photonic bandgap (PBG) periodic structure is utilized as an isolator slab to repress the mutual coupling in densely packed array antenna for SAR and MIMO applications as displayed in Fig.20. By this method, the MTM PBG layout is exhibited to efficiently reduce surface-wave distributions between the patch arrays by an average of 12dB, see Table XII.…”
Section: J Decoupling Improvement Of Adjacent Array Antennas With Pementioning
confidence: 99%
See 1 more Smart Citation
“…In [134] an MTM photonic bandgap (PBG) periodic structure is utilized as an isolator slab to repress the mutual coupling in densely packed array antenna for SAR and MIMO applications as displayed in Fig.20. By this method, the MTM PBG layout is exhibited to efficiently reduce surface-wave distributions between the patch arrays by an average of 12dB, see Table XII.…”
Section: J Decoupling Improvement Of Adjacent Array Antennas With Pementioning
confidence: 99%
“…This explains that the radiation specifications are not intensely influenced by realizing the MTM PBG decoupling frame. empirical Sparameters of the arrays without (WO) and with (W) proposed isolator, (f) input impedances (Ω) after apply the periodic MTM-PBG isolator, (g) circuit model including MTM-PBG isolator sheet, (h) gain curve, (i) radiation efficiency curve, and (j) experimental radiation patterns before and after the periodic MTM-PBG isolator [134]. Table XIII shows comparisons in the performance parameters of the abovementioned techniques relative to the studied literature in terms of the mutual coupling reduction techniques, maximum isolation improvement, number of applied elements in the array structure, design complexity and simplicity, impact on the size after applying the technique, and augmentation and development of the array after applying the technique.…”
Section: J Decoupling Improvement Of Adjacent Array Antennas With Pementioning
confidence: 99%
“…These last are a composite media made up of an arrangement of metal structures on the surface of dielectric substrates. They can be engineered to have unique electromagnetic properties and integrated after in antenna design to exhibit many application requirements [4][5][6]. In other researches, metamaterials structures are applied in RFID (radio frequency identification) tags in order to augment the read range and to decouple the tag with the tagged object [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mutual coupling among neighboring radiating elements in the antenna can be improved by increasing the space between the elements, but this is at the cost of increased antenna size [20]. Many techniques have been investigated to reduce mutual coupling between elements, which include using metamaterials [21][22][23][24][25], metasurface [26][27][28], and embedded periphery slot [29]. The results show that the presence of these components close to a radiating element can affect its resonant frequency.…”
Section: Introductionmentioning
confidence: 99%